The Potential of Coral Reef as Support of Marine Ectourisme at Sidodadi Village, Pesawaran Regency, Province of Lampung - Kusuma, Anma Hari (Jurnal Biologi Tropis, 2024)
Coral reefs can be used for marine ecotourism by considering suitability and carrying capacity analysis. The aim of this research is to analyze the potential of coral as a support for marine ecotourism in Sidodadi Village, Teluk Pandan District, Pesawaran Regency, Province of Lampung. Data collection on the percentage of cover and type of growth (life form) of coral was carried out using the Underwater Photo Transect (UPT) method, while coral fish used the Underwater Visual Census (UVC) method. The results of the research show that the physico-chemical parameter conditions of the waters are suitable for marine ecotourism, coral cover ranges from 0,12-78,03%, 523 reef fish consist of 7 major fish families, 5 target fish families and 1 indicator fish family, suitability tourism at each station in the research location where station 1 is 59,25% (Conditionally Appropriate), station 2 is less than 40,74% (Not Appropriate), station 3 is 88,88% (Suitable) and station 4 is 59,25% (Conditionally Appropriate). The area's carrying capacity is 106 people/day and the utilization carrying capacity is 11 people/day.